ANALISIS TINGKAT KENYAMANAN TERMIS DI WILAYAH KOTA TANGERANG BERDASARKAN THI (TEMPERATURE HUMIDITY INDEX) - Pertiwi, Dyah Ajeng Sekar (Jurnal Widya Climago, 2021)
The geographical location of an area has an impact on the physiological comfort in a residential area. In addition, the rapid development and climate change also have an impact on weather parameters that affect the level of comfort. This research was conducted to determine the comfort level in Banten Province using THI (Temperature Humidity Index) analysis of the parameters of air temperature and humidity. The value of the comfort level is divided using a comfort interval, for THI values between 21-24 °C there are 100% of the population declaring comfortable, THI between 25-27 °C only 50% of the population feels partially comfortable, and THI> 27 °C as much as 100% the population feels uncomfortable. Based on climate data from 1986 - 2009 at Serang Meteorological Station, Cengkareng Meteorological Station and South Tangerang Climatology Station, the results showed an average percentage of daily comfort levels with a comfortable category of 9,5% (35 days per year), some comfortable 79,2% (289 days per year) and uncomfortable 11,3% (41 days per year). During this period, there was an increase in the THI index in Banten Province which tended to be increasingly uncomfortable with the South Tangerang Climatology Station being the most significant area.